Correlates of mother-infant interaction and self-regulation in a perinatal intervention program - Fehringer, Karen A., author; Morgan, George, advisor; Harmon, Robert J., committee member; Lehmann, Jean, committee member; Davies, Patti, committee member (Colorado State University. Libraries, 2003)
The purposes of this study are to investigate whether the number of nurse home visits during pregnancy and the early postnatal period is related to mother-infant interactions and infant's patterns of self-regulation, whether these interactions change over the course of the first six weeks of life, and if demographic variables are related to mother-infant interactions and sleep patterns. A fourth purpose is to learn about the timing and topics for presentation of educational materials, and about support systems during pregnancy. Twenty-three low-income, first time mothers completed the two week feeding and teaching session, using the Nursing Child Assessment Satellite Training (NCAST) feeding scale. Nineteen mother-infant dyads completed both the two week and six week feeding observations and the exit interview. Sixteen mothers completed the Sleep Activity Record (SAR). Statistically significant (p < .05) results from the feeding observation are as follows: a) mothers who had more education had a higher caregiver total score at two weeks and six weeks, b) infants of mothers with more education had a higher infant total score at two weeks, and c) the dyad had a higher total contingency (reciprocal interaction) score at two weeks. Mothers in households with higher levels of income had higher contingency scores at 6 weeks, and the change in the contingency score from two to six weeks was positive for mothers with more income. The cluster of positive findings related to the SAR is that infants who had a higher total score at 2 weeks received more feedings at 3-4 weeks. Mothers reported that the medical and health education information of the nurses was valuable during the pregnancy and after the birth of the baby. Mothers appreciated the social support of the nurses and credited them with being an important part of the support network. A larger sample size pooled from multiple sites, a longer time period for intervention and data collection, and serial SAR recordings might yield more significant results. Further investigation into topics covered, the timing of education for pregnant and parenting women, and the role of social supports may provide information to shape policy and funding considerations.
Keywords: nursing; public health; mothers; babies; home health care; perinatal care; intervention